Prawda marginesu (notatki z lektury) - Próchniak, Paweł (Poznańskie Studia Polonistyczne. Seria Literacka, 2012)
The essay presents remarks about the category of “the margin” in modern Polish literature, and also an interpretation of Zbigniew Kopeć’s book, Niepokorni. Brudni. Źli. Ludzie marginesu w prozie polskiej XX wieku [The Angry, The Dirty, The Bad: People of the Margin in Polish Fiction of the 20th Century]. The truth of the margin emerges from an encounter with sheer existence, with life on the bottom, in places marked by suffering and evil, places that are sick, pathological, revulsive, and consequently abandoned by the better-off part of the society. A lit erature that approaches such places attempts to be a quest for pure and simple truth that is touching and deeply human. Kopeć’s and the present author’s remarks, presented in the article, are dedicated to such attempth made by Polish fiction writers of the 20th century.